2012
DOI: 10.1017/jfm.2012.364
|View full text |Cite
|
Sign up to set email alerts
|

The surface signature of internal waves

Abstract: Oceans that are stratified by density into distinct layers support internal waves. An internal soliton gives rise to characteristic features on the surface, a signature of its presence, in the form of a ‘rip’ region, as reported in Osborne & Burch (Science, vol. 208, 1980, pp. 451–460), which results in a change in reflectance as seen in NASA photographs from the space shuttle. In the present paper, we give a new analysis of this signature of an internal soliton, and the ‘mill pond’ effect of an almost com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 28 publications
3
74
0
Order By: Relevance
“…However, in a related problem, Craig et al [26] highlighted the physical relevance of resonance between internal and surface waves in a two-layer ocean when the speeds are different, and a similar study may be performed in the present configuration.…”
Section: Results (A) One Elastic Platementioning
confidence: 74%
“…However, in a related problem, Craig et al [26] highlighted the physical relevance of resonance between internal and surface waves in a two-layer ocean when the speeds are different, and a similar study may be performed in the present configuration.…”
Section: Results (A) One Elastic Platementioning
confidence: 74%
“…These reduced models mostly focus on either the dynamics of short-mode waves around the resonant k res at sufficiently long times or the linear modulations and the traveling wave solutions for short-mode surface waves. A particularly detailed prior discussion of surface signature phenomena was presented in (Craig et al 2012) using a coupled Korteweg-de Vries (KdV) and linear Schrödinger model (we compare this model with ours in appendix D). However, an intuitive understanding of the surface signature phenomena was still lacking, especially for the asymmetric behavior of SWs at the leading and trailing edges.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(ii) Resonant excitations: The rough region travels along with the internal wave; that is, the SW group velocity is close to the internal-wave phase velocity (Osborne & Burch 1980;Kropfli et al 1999;Hwung et al 2009;Craig et al 2012). To understand the above two surface phenomena, we numerically study the surfacewave and interfacial-wave (IW) manifestation in a two-layer, density-stratified system using a weakly nonlinear Boussinesq-type model.…”
Section: Introductionmentioning
confidence: 99%
“…Class 3 triad resonance is believed to be responsible for the surface signature of the underlying internal waves [17,29,35,38]. The TWN model possesses two-mode waves, one slow and the other fast, and thus resonant interactions among different modes can occur during the energy exchange process [more details can be found in Appendix B].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(3.31). Many early results [1,16,17,27,41] have confirmed that there exists a unique resonant wavenumber, denoted by k res , satisfying Eq. (2.50) in the two-layer fluid system.…”
Section: B Class 3 Triad Resonance Conditionmentioning
confidence: 99%